Enhancing evidence-informed decision-making in Ethiopia's animal health sector with Global Burden of Animal Diseases support: Game learning of evidence ecosystem - Dinede, Getachew; Keba, Abdi; Amenu, Kebede; Makau, D.; Grace, Delia (International Livestock Research Institute, 2024)
This report presents the findings from two workshops. In the first workshop held on 15 April 2024, participants answered survey questions designed to assess their institutes' evidence ecosystems, including evidence production and use of evidence for planning, resource allocation, and implementation of various activities. They also answered questions related to identifying the factors that facilitate and hinder the use of evidence in their institutes. In the second workshop held on 16 April 2024, participants worked on simulation exercises related to the management of Rift Valley fever outbreak progressions.